Competition and gender prejudice : are discriminatory employers doomed to fail? - Andrea Maria Weber; Christine Zulehner (Center for Economic Studies and ifo Institute (CESifo), 2009)
According to Becker's (1957) famous theory on discrimination, entrepreneurs with a strong prejudice against female workers forgo profits by submitting to their tastes. In a competitive market their firms lack efficiency and are therefore forced to leave. We present new empirical evidence for this prediction by studying the survival of startup firms in a large longitudinal matched employer-employee data set from Austria. Our results show that firms with strong preferences for discrimination, i.e. a low share of female employees relatively to the industry average, have significantly shorter survival rates. This is especially relevant for firms starting out with female shares in the lower tail of the distribution. They exit about 18 months earlier than firms with a median share of females. We see no differences in survival between firms at the top of the female share distribution and at the median, though. We further document that highly discriminatory firms that manage to survive submit to market powers and increase their female workforce over time.
Keywords: J16; J71; L25; 330; firm survival; profitability; female employment; discrimination; market test; matched employer-employee data; Frauenerwerbstätigkeit; Geschlechterdiskriminierung; Unternehmensgründung; Unternehmensentwicklung; Rentabilität; Österreich